2016
DOI: 10.4028/www.scientific.net/msf.879.151
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Molecular Motion Cooperativity in Polymeric and Metallic Glass-Forming Liquids

Abstract: In order to investigate the relationship between the bonding nature and the cooperative relaxation, a comparative study of the relaxation behavior in polymeric and metallic glass forming systems has been performed based on the Bond Strength–Coordination Number Fluctuation (BSCNF) model developed by the authors. In the present work, we studied the correlations between the fragility m, the Vogel temperature T0, the degree of molecular cooperativity NB, and the Kohlrausch exponent βKWW. The results show that T0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Regarding the cooperativity of atomic dynamics in supercooled liquids, our analysis based on the Bond Strength-Coordination Number Fluctuation model [21] indicates that the number of structural units involved vary with temperature [22]. The connection of such a cooperativity with the fragility has been also investigated [23].…”
Section: Structural Alloysmentioning
confidence: 99%
“…Regarding the cooperativity of atomic dynamics in supercooled liquids, our analysis based on the Bond Strength-Coordination Number Fluctuation model [21] indicates that the number of structural units involved vary with temperature [22]. The connection of such a cooperativity with the fragility has been also investigated [23].…”
Section: Structural Alloysmentioning
confidence: 99%
“…( 6) and ( 7), we obtain 𝑁 B = ln 10 𝑚 𝐶 ⁄ , that is, if we have the values of the fragility and the parameter 𝐶, we get information on the number of structural units that is involved in the cooperative movement. The above expression has been used to examine the cooperativity of various type of materials [24][25][26]. In particular, for the case of polymers, it has been found that 𝑁 B varies roughly between 20 and 80 [26].…”
Section: Samplementioning
confidence: 99%
“…The above expression has been used to examine the cooperativity of various type of materials [24][25][26]. In particular, for the case of polymers, it has been found that 𝑁 B varies roughly between 20 and 80 [26].…”
Section: Samplementioning
confidence: 99%